A Translation Analysis Of Deixis In The Dream Of Trespass Novel By Fatimah Mernissi And Its Translation (Pragmatic Perspective) - Putra, Untung Wisuda Purnama; , Dra. Dwi Haryanti, M. Hum; , Siti Fatimah, S. Pd, M. Hum (2014)
This research belongs to a qualitative research. The researcher tries to identify the types of deixis and the equivalence of deixis in The Dream of Trespass novel by Fatimah Mernissi and its Translation. The object of the research is the novel The Dream of Trespass written by Fatimah Mernissi that consists of 226 pages. It is translated into Indonesian novel Harem by Amad Baiquni. In collecting the data, the researcher uses the document. The data in this research are sentences containing deixis, they are personal deixis, place deixis, time deixis, discourse deixis and social deixis. The data are analized based on the theories, the knowledge and desire of the researcher related to the problem statements. From the collected data, the researcher finds 202 data of English deixis and equivalence. The result of the research shows that : based on the equivalent and non equivalent deixis from 202 data of the research, the data involved in: (a) the equivalent deixis which are translated into Indonesian are 183 data or 90,6%, (b) the non equivalence deixis which are translated into Indonesian are 19 data or 9,4. It means that the translation analysis of deixis in novel Dream of Trespass is very good.